Traffic Related Air Pollution and Transplant Failure. (June 2017) - Pierotti, Livia; Collet, David; Schofield, Susie; Fecht, Daniella; De Hoogh, K.K.; Cullinan, Paul
Abstract : Background: There is limited evidence that exposure to traffic related air pollution is associated with the development of chronic lung allograft dysfunction and graft failure among lung transplant recipients. The aim of the study is to explore associations between traffic related air pollution and transplant failure among lung and other solid organ transplant recipients in Great Britain. Methods: All lung, heart, liver, and kidney transplants between 2000 and 2008 were included. The last follow up date was 2 nd March 2015. Using residential postcode at time of transplant, we calculated distance to nearest road and distance to nearest major road. In addition, annual average air pollution exposures were modelled for each transplant recipient, including nitrogen dioxide, nitrogen oxides and particulate matter (PM10, PM2.5 ). Cox regression models were fitted to assess associations between each air pollutant and transplant failure after adjustment for age, sex, transplant year and donor age/smoking status. Results: 780 lung, 1213 heart, 3650 liver and 11966 graft kidney transplant patients were included in the analysis. The estimated median follow up time (years) was 9.1, 10.0, 9.1 and 8.8 for lung, heart, liver and kidney respectively. We did not find any consistent association between first lung, liver and kidney transplant failure and any of the analysed air pollutants. Conclusions: Our analysis does not confirm associations between traffic related air pollution exposure and the risk of transplant failure as reported by previous studies.